Redesign policy for a system with uncertain failure rates - Ge, Qianru; Atan, Zümbül; van Jaarsveld, Willem (Operations research letters, 2024)
Consider a newly developed system sold under a performance based contract (PBC), and subject to failures following various failure modes. Redesign may address certain failure modes. To trade-off redesign costs and costs associated with the PBC, we find the optimal failure modes to redesign based on the current beliefs on the failure rate per failure mode, and the amount of time remaining under the PBC. We develop analytic insights into the structure of the optimal policy.